The Level of Inclusion of Bioethical Issues in the ‎Yemeni School Biology Textbooks - Al-Jaji, Raja (Jordan Journal of Educational Sciences, 2022)
This study aimed to investigate the inclusion of bioethical issues in high schools’ biology textbooks in Yemen. The study sample consists of three biology textbooks of Yemeni high schools. Qualitative content analysis methodology was adopted and the unit of the analysis was the bioethical issue theme. The tool of the study consists of 9 bioethical issues namely, Cloning, Stem Cells, Gene Therapy, Embryo Cryopreservation, Euthanasia, Surrogate Mother, Genetic Imprint, Organ Transplantation and Genetically Modified Food. The results showed that there is no inclusion of bioethical issues in the biology textbooks for the 10th grade and the 11th grade. The results also showed that the 12th biology textbook has the best inclusion of the bioethical issues. However, the study indicated that there is a major deficiency in including bioethical issues in biology textbooks